Pertimbangan Penyidik Dalam Penetapan Status Tersangka Dalam Kasus Video Porno - Oktovianus Nurlatu; Elsa Rina Maya Toule; Julianus Edwin Latupeirissa (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Determition of GA as a suspect in the case of his personal pornographic video, together with MYD, on GA social media, he was charged with the prohibition of article 4 paragrahp (1) of law number 44 of 2008 concerning pornography, article 4 paragraph (1) in its explanation of making and for its own sake. And GA is a victim, but in fact investigators set GA as a suspect.Purposes of the Research: Explain about what is the basis for determining GA as a suspect in a porn video case and proving pornographic elements in the determination of GA as a suspect in a porn video case.Methods of the Research: The type of research used is normative juridical research. The approach to the problem used is a statutory approach that prioritizes legal materials and a case approach.Results of the Research: Based on the results of the study, it can be concluded that it is based on preliminnary evidence, namely evidence of  GA’s confession and evidence of  a 19-second video clue that exists who  confirm that the person in the 19-second porn video is GA.that GA’s actions meet the qualifications of the elemens of article 4 paragraph (1) in conjunction with  article 29 of the pornography law, related to the elements of his actions, namely producing and making, as well as elemens of the object of his actions, namely making videos of sexual activities with MYD and fulfilling the qualifications of the elemens of article 8 juncto article 34 of the pornography law, namely subjective elements and objective elemens because they intentionally or with their consent become objects containing pornography law in the future,it can be emphasized so that in carrying  out law enforcement efforts related to pornograhy cases it will be better without violating the human rights of the community.